VICTIMS OF FAMILY VIOLENCE: PSYCHOLOGICAL EFFECTS ON CHILDREN OF ABUSED WOMEN - Patró Hernández, Rosa; Limiñana Gras, Rosa María (Anales de Psicología / Annals of Psychology, 2005)
Women and children are the main victims of domestic or family violence. The amount of research on abused women and aid resources for them is increasing. However, scarce attention is paid to their children. The aim of this article is to highlight the serious consequences for children who have grown up in violent homes and who have been victims or witnesses to family violence. We intend to stress the traumatic aspect of this experience and the basic guidelines which should be followed to manage and prevent violent behaviours in these children.